British Policy Towards the Balkans - Kolakovic, Aleksandra M. (Sociološki pregled, 2018)
Review opinion of the Aleksandar Rastović’s book Great Britain and the Kosovo Vilayet 1877-1912, Zavod za udžbenike, Beograd, 2015, pp. 256Formulation of British policy towards the Balkans and Serbia, through historical processes of long duration, is one of the most important and under-researched topic in the spite of numerous books, articles and texts. Publication of the book Great Britain and Kosovo Vilayet 1877-1912, written by prof. Dr. Aleksandar Rastović, who has dedicated himself to the study of the British-Serbian relations since the beginning of his academic career, launches a new scholarly discussion.Keywords: Great Britain, the Balkans, Serbia, Kosovo Vilayet, the end of the 19th and beginning of the 20th century.